Pengaruh Citra Merek, Persepsi Harga, dan Kualitas Produk Terhadap Kepuasan Pelanggan Teh Celup Poci di Mojokerto - Olifiana, Aulia; Soebiantoro, Ugy (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the industrial fields that experience fierce competition is the industry in the beverage sector. Currently the beverage industry that is being favored by consumers is tea. One of them is Tea Poci. This study aims to determine the influence of brand image, price perception, and product quality on customer satisfaction of teabag pots in Mojokerto. The research method used is nonprobability sampling with purposive sampling techniques. The population in this study is customers who have purchased Poci Tea Bags more than 1 time in Mojokerto who are at least 17 years old. The sample of this study was 98 respondents. The analysis method used is Partial Least Square. The results showed that brand image, price perception, and product quality had a positive influence on customer satisfaction. Keywords: Brand Image, Price Perception, Product Quality, Customer Satisfaction